Design and evaluation of antifungal vaginal suppository using coconut oil as base for vulvovaginal candidiasis - Ayomide D. Mustapha; Folusho M. Oyedepo; Olufunke D. Akin-Ajani; Oluwatoyin A. Odeku (SpringerOpen, 2023)
Abstract Background The emergence of antimicrobial resistance to antifungals has made vulvovaginal candidiasis a concern. Coconut oil has antimycotic properties that could have a synergistic effect when combined with antifungals. Thus, clotrimazole suppositories were prepared using coconut oil as a base to improve its use and delivery in antimycotic treatment and the suppositories were evaluated for their physicochemical, mechanical, and drug release properties, and the antimycotic effect of clotrimazole and coconut oil was examined singly and in combination, as well as their formulations using the agar-well diffusion method in comparison with polyethylene glycol (PEG), and cocoa butter bases. Using the fusion method, coconut oil was solidified with beeswax (20-50%) to prepare 100 mg clotrimazole suppositories. Surfactants (4% w/w); Tween 20®, Span 20®, sodium lauryl sulphate, and their combinations (3% w/w ratio 1:1 of Tween 20® and Span 20®) were used to improve the rate of drug release from the suppository. Results The suppositories had a pH of 4.1-6.0 and crushing strengths of 0.53 ± 0.07-32.56 ± 5.42 N. Suppositories containing surfactants and those prepared from PEG had significantly (p < 0.05) lower disintegration times ranging from 35 to 90 min than those without surfactants ranging from 305 to 388 min. Drug release (t 80) was the fastest from the suppositories containing 40% coconut oil, Tween 20, and PEG. Using the Korsmeyer-Peppas' model, suppositories made from PEG had a non-Fickian diffusion, while those containing 40% coconut oil, and Tween 20 had a super case II transport mechanism. The combination of clotrimazole and coconut oil gave higher zones of inhibition against Candida species compared to either clotrimazole or coconut oil alone. The formulations had higher antimycotic activities against Candida albicans than Candida krusei and Candida tropicalis. Conclusion The optimized formulation with the desired physicochemical and drug release properties was obtained with coconut oil (40% w/w) solidified with beeswax (50% w/w) as a base. Coconut oil appeared to possess a synergistic antimycotic effect on clotrimazole. Thus, clotrimazole vaginal suppositories with coconut oil as a base in the treatment of vulvovaginal candidiasis showed potential against C. albicans and other Candida species. Graphical abstract